The nutritional quality improvement of dried gluten free pasta supplemented with Cladophora spp. - Choobthaisong, Patchareeporn; Oupathumpanont, Orawan (Emirates Journal of Food and Agriculture, 2021)
This research aimed to study: 1) the suitable formula gluten free pasta supplemented with Cladophora spp., 2) the chemical and physical properties of pasta supplemented with Cladophora spp., and 3) the consumer acceptance. A mixture design experiment was conducted, and three factors were analyzed, 50-70% brown rice flour, 15-25%modified starch, and 10-20%Cladophora spp., the most suitable formula indicated 68%brown rice, 22%modified starch, 10%Cladophora spp. The nutritional profile of this gluten-free pasta per 100 grams was 379.00 kilocalories of total energy, 7.09 grams of protein, 1.91 grams of dietary fiber, 0.11 milligrams of vitamin B, 0.11 milligrams of vitamin B2, 31.30 milligrams of calcium, and 3.84 milligrams of iron and antioxidant activity 48.50 mg eq Trolox. Most consumers’ overall liking score was at a moderate level. The gluten-free pasta supplemented with Cladophora spp. will make better nutrition value.